Relative and absolute reliability of isometric and isokinetic shoulder maximal moment and flexion/extension ratios in gymnasts - Milosis, D. C.; Siatras, T. A.; Christoulas, K. I.; Patikas, D. A. (Science of Gymnastics Journal, 2018)
Shoulder strength is essential for gymnasts in order to succeed in their sport, but little research has examined isometric and isokinetic shoulder moment and flexion/extension ratios. The purpose of this study was to evaluate the relative and absolute reliability of isometric and isokinetic shoulder moment and shoulder flexion/extension ratios. Fifteen international level male gymnasts (age: 19.3 ± 2.3 years) participated in the study. Two identical measurements with one week interval were applied using the isokinetic Humac Norm 770 dynamometer at three angles (45º, 90º, and 135º) for isometric and at three angular velocities (60º/s, 180º/s, and 300º/s) for concentric and eccentric action modes. All measurements were conducted in a range of motion of 10º to 180º, in supine position, bilaterally, with the elbows fully extended. Notwithstanding a small systematic bias (due to testing/learning) from measurement 1 to measurement 2 significant in four parameters, the results supported the reliability of the measurements. Relative (a) and absolute (b) reliability values were ranged as follows: (a) intraclass correlation coef?cient (ICC) 0.73 to 0.96 and (b) standard error of measurement (SEM)(%) (calculated using ICC) 3.4 to 11.2%, minimum detectable change (MDC)(%) 10.7 to 31.1%, SEMe(%) (calculated using mean square error) 0.1 to 23.4%, MDCe(%) 1.6 to 48.8%, and coef?cient of variation (CV)(%) 8.6 to 17.8%. Bland-Altman analysis showed that the bias was lower than 10% and limits of agreement (LOAs) were lower than 35%. SEMe(%) and MDCe(%) were considered as more important and meaningful to detect any significant change between two measurements, or to detect muscle imbalances. Considering the limitations of the study, results from the present study provided assessment methods and normative data that could be very helpful for researchers and practitioners to evaluate the effectiveness of intervention programs aiming at the development of shoulder muscle strength.